Sistema penitenciário cearense: a dificuldade da ressocialização - Aguiar, Camila Pessoa de (2007)
This research has for target to build a picture of the present penitentiary system in estate of Ceará, in order to analyze the existence of "ressocialization" of the penalty as a direction for criminal politics. At first, it is analyzed the origin and historical evolution of the prison penalty. In the second section, the purposes of liberty privation penalty are studied. In the third topic, it is shown how law expect the penal institutions to be. At last, it is analyzes some of the estate of Ceará's penal units. It is concluded that, although some notable advances, still becomes necessary a engagement from estate of Ceará's authorities and community in order to guarantee to the prisoner a decent execution of his penalty, so that, once free, they can hope to fight for triumph.